Scientific data exchange: a schema for HDF5‐based storage of raw and analyzed data. (3rd October 2014) - De Carlo, Francesco; Gürsoy, Dogˇa; Marone, Federica; Rivers, Mark; Parkinson, Dilworth Y.; Khan, Faisal; Schwarz, Nicholas; Vine, David J.; Vogt, Stefan; Gleber, Sophie‐Charlotte; Narayanan, Suresh; Newville, Matt; et al.
<x xml:space="preserve">Abstract</x> Data Exchange is a simple data model designed to interface, or `exchange', data among different instruments, and to enable sharing of data analysis tools. Data Exchange focuses on technique rather than instrument descriptions, and on provenance tracking of analysis steps and results. In this paper the successful application of the Data Exchange model to a variety of X‐ray techniques, including tomography, fluorescence spectroscopy, fluorescence tomography and photon correlation spectroscopy, is described.